Implementation of Confiscation of Beneficial Owner Assets in Money Laundering Cases (Case Study of Ratu Atut Chosyiah) - Ridho, Rahmad; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. In the national legal framework, the concept of discussion on money laundering was first formulated and enforced in Law Number 15 of 2002 concerning the Crime of Money Laundering. This law was then updated and revised again in Law Number 25 of 2003. The existence of this law is expected by the State (government) to end money laundering, strengthen law enforcement considering the inadequate human resources involved in money laundering cases, and take a new approach to international collaboration in increasingly complex money laundering cases. Law Number 15 of 2002 concerning Money Laundering Crimes explicitly states that money that is laundered generally comes from criminal acts, including corruption as one of its main sources. The perpetrators will try to keep the proceeds of the crime away from their original source and camouflage them in the form of assets that appear legal. Furthermore, money laundering is defined as a set of procedures carried out to change the status of money from criminal acts-which is legally considered illegitimate or haram-into clean and acceptable income according to applicable laws. In practice, asset forfeiture not only functions as a repressive tool, but also as a preventive measure to prevent the shifting or escape of assets to other parties. Unfortunately, until now, the Draft Law on Asset Confiscation which is expected to provide a strong legal basis, is still stuck on the legislator's desk and has not been a priority in the National Legislation Program (Prolegnas).